The Quality of Housing in Four Roma Communities Living on the Periphery of Făgăraş City, Romania: Differences in Perception between Roma and Romanians - Rezeanu, Cătălina-Ionela (Calitatea Vieții, 2015)
This study is a secondary analysis of data based on “The Barometer Survey on Roma in Făgăraş”, conducted in 2013. Quantitative data were collected through the oral survey technique based on standardized questionnaire, applied to the peripheral areas of Făgăraş City (Combinat Colony, Negoiu Street, Prunului Street, and Plopului Street), where Roma communities face severe housing problems (systematic sample, N = 400 Roma respondents aged 18 years and over) and to the central and middle city neighborhoods, majority inhabited by Romanians (systematic sample, N = 400 Romanian respondents aged 18 years and over). Through this study we intend to expose the housing situation of Roma by comparing Roma self-perceptions and Romanian perceptions about Roma. The following dimensions of quality of housing were measured: housing and household characteristics; satisfaction with housing situation; agenda of housing problems; solutions for improving housing situation. Additionally, the following aspects of Roma situation were measured: social distance towards the Roma, prejudice and discrimination against Roma. Overall, data showed that Romanians center more than Roma on the Roma lack of jobs issue, and those who think that the solution to Roma housing issue would be to move Roma elsewhere do not perceive as much as Roma that this solution would improve Roma housing conditions and do not take into account that Roma do not want to be moved at the periphery of the city. Furthermore, Romanians do not have the same opinions as Roma regarding the magnitude of public discrimination against Roma, and also they perceive more than Roma a lack of trust between the Roma and Romanian people.